A positive electrode sheet and its preparation method and electrical equipment
By introducing carboxy modified carbon quantum dots and lithium supplement agents into the positive electrode sheet of lithium-ion batteries, and forming ester bond connections through esterification reaction, the problem of insufficient circulation performance and safety of existing lithium-ion batteries is solved, and the problem of insufficient circulation performance and safety of existing lithium-ion batteries is achieved. Higher battery performance and safety.
Patent Information
- Application Number
- CN202411547369.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-01
AI Technical Summary
Existing lithium-ion batteries have limitations in circulation performance and safety, resulting in battery capacity decay and safety hazards.
A positive electrode sheet is adopted, which includes a current collector modified by hydroxyl group and an active layer disposed on the surface of the current collector. The active layer contains a carboxy modified carbon quantum dot and a lithium supplement agent to form an ester bond through an esterification reaction. Connect the current collector and the active layer.
It improves the battery's conductivity, ion transmission performance, mechanical stability and cyclic stability, reduces the pole plate impedance, extends the battery's cycle life and improves safety.
Smart Images

Figure CN119069709B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a positive electrode plate and a preparation method thereof and electrical equipment. Background Art
[0002] As the main power source for modern electronic devices and electric vehicles, lithium-ion batteries are widely used due to their high energy density, long cycle life and low self-discharge rate. Cycle performance and safety are two key indicators of battery performance, which directly affect the battery's service life and safety.
[0003] Existing lithium-ion battery technology mainly relies on the optimization of key components such as positive and negative electrode materials, electrolytes and diaphragms. The positive electrode materials usually use lithium transition metal oxides, such as lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide and lithium iron phosphate, while the negative electrode materials are mostly graphite or silicon-based materials. The selection and ratio of these materials have a direct impact on the performance of the battery. In terms of electrolytes, organic solvents containing lithium salts are usually used, such as lithium hexafluorophosphate dissolved in carbonate solvents. The diaphragm is used to isolate the positive and negative electrodes to prevent short circuits while allowing the transmission of lithium ions.
[0004] However, poor cycle performance is a major challenge facing existing lithium batteries. During the battery's charge and discharge cycle, the structure of the positive and negative electrode materials may undergo irreversible changes, causing the battery capacity to gradually decay. In addition, the decomposition of the electrolyte and the aging of the diaphragm will also affect the battery's cycle stability. Safety issues should not be ignored either. Lithium-ion batteries may experience thermal runaway under abnormal conditions such as overcharge, overdischarge, high temperature or mechanical damage, posing a safety hazard to users.
[0005] In summary, existing lithium-ion battery technology has certain limitations in terms of cycle performance and safety. The battery's insufficient cycle stability causes its capacity to decay after long-term use, affecting the user experience. At the same time, the battery's safety issues under extreme conditions also limit its use in certain application scenarios. The existence of these problems not only affects the reliability and economy of lithium-ion batteries, but also puts forward higher technical requirements for battery manufacturers. There is an urgent need to develop new lithium-ion battery technologies with better cycle performance and higher safety. Summary of the invention
[0006] The first purpose of the present invention is to provide a positive electrode plate and a preparation method thereof and electrical equipment, wherein the electrode plate can reduce the plate impedance and improve the battery cycle performance and other advantages.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0008] In a first aspect, the present invention provides a positive electrode sheet, comprising:
[0009] A current collector and an active layer disposed on a surface of the current collector;
[0010] The surface of the current collector contains hydroxyl groups introduced by hydroxyl modification treatment;
[0011] The active layer includes carbon quantum dots and a lithium supplement; the surface of the carbon quantum dots contains carboxyl groups introduced by carboxyl modification treatment;
[0012] The surface of the current collector and the carbon quantum dots in the active layer are connected via ester bonds formed by an esterification reaction between the hydroxyl groups and the carboxyl groups.
[0013] In an optional embodiment, the positive electrode plate further includes a functional layer disposed between the current collector and the active layer;
[0014] The functional layer includes a coating area and a non-coating area;
[0015] The coating region includes an organic polymer;
[0016] In the non-coating area, the active layer is directly connected to the surface of the current collector.
[0017] In an optional embodiment, the organic polymer includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyimide, aramid or polyether.
[0018] In an optional embodiment, the coating area further includes a porous inorganic material;
[0019] The organic polymer can be fully or partially disposed in the pores of the porous inorganic material.
[0020] In an optional embodiment, the porous inorganic material includes at least one of aluminum oxide, titanium oxide, zirconium oxide, silicon oxide, manganese oxide, magnesium oxide, nickel oxide, boron nitride, aluminum nitride, magnesium nitride, silicon nitride, aluminum fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride, barium fluoride, aluminum hydroxide and boehmite.
[0021] In an optional embodiment, the area of the coating region does not exceed 30% of the total surface area of the current collector.
[0022] In an optional embodiment, the lithium supplement agent is a nano lithium supplement agent;
[0023] The lithium supplement includes at least one of lithium oxalate, lithium nitride, lithium nickelate, lithium cobaltate and lithium ferrite.
[0024] In a second aspect, the present invention provides a method for preparing a positive electrode sheet as described in any one of the aforementioned embodiments, comprising:
[0025] An active material slurry is coated on the surface of the current collector treated with hydroxyl group modification to obtain a positive electrode plate; wherein the active material slurry includes carbon quantum dots treated with carboxyl group modification and a lithium supplement agent.
[0026] In an optional embodiment, the active material slurry is coated on the surface of the current collector treated with hydroxyl group modification to obtain a positive electrode sheet, comprising:
[0027] The current collector is immersed in a solution containing hydroxyl groups, and after drying, the current collector modified with hydroxyl groups is obtained;
[0028] The carbon quantum dots and the lithium supplement agent are added into an organic solvent and dissolved to obtain the active material slurry; and the active material slurry is coated on the surface of the current collector treated with hydroxyl group modification to form an active layer;
[0029] The positive electrode sheet is obtained by drying and rolling.
[0030] In an optional embodiment, the active layer further includes a positive electrode active material, a conductive agent and a binder.
[0031] In an optional embodiment, before coating the active material slurry, the method further comprises:
[0032] Prepare a functional slurry; the functional slurry includes an organic polymer; or the functional slurry includes an organic polymer and a porous inorganic material;
[0033] The functional slurry is coated on the surface of the current collector treated with hydroxyl group modification, so that a functional layer is formed on the surface of the current collector; the functional layer includes a coating area coated with the functional slurry and a non-coating area not coated with the functional slurry;
[0034] The active material slurry is coated on the surface of the current collector treated with hydroxyl group modification to form an active layer, comprising:
[0035] The active material slurry is coated on the surface of the coating area and the surface of the non-coating area where the current collector is exposed to form the active layer.
[0036] In a third aspect, the present invention provides a battery, comprising a positive electrode sheet as described in any one of the aforementioned embodiments, or a positive electrode sheet obtained by the preparation method as described in any one of the aforementioned embodiments.
[0037] In a fourth aspect, the present invention provides an electrical device, comprising the battery as described in the above embodiment.
[0038] Compared with the prior art, the electrode plate provided by the present invention has the following beneficial effects:
[0039] (1) Enhanced conductivity: The carboxyl-modified carbon quantum dots set in the active layer can significantly improve the conductivity of the electrode due to their unique physical and chemical properties. Carbon quantum dots have high conductivity and can form an effective electron transport network inside the electrode material, thereby reducing the internal resistance of the battery and improving the battery's charge and discharge efficiency.
[0040] (2) Improved ion transport performance: The introduction of carboxyl-modified carbon quantum dots not only improves the electron transport efficiency, but also helps improve the lithium ion transport performance in the active layer. The high specific surface area and porous structure of carbon quantum dots provide more transport channels for lithium ions, reducing the diffusion resistance of lithium ions in the electrode material, thereby improving the rate performance and cycle stability of the battery.
[0041] (3) Tightly connect the active layer and the current collector: Through the esterification reaction between the hydroxyl-modified current collector surface and the carboxyl-modified carbon quantum dots, a stable ester bond is formed. This chemical bonding method makes the connection between the active layer and the current collector tighter, enhances the mechanical stability of the electrode structure, reduces the shedding and peeling of active materials during the battery charging and discharging process, and thus improves the cycle life of the battery.
[0042] (4) Reduce the electrode impedance: The tight ester bond connection reduces the interface impedance between the active layer and the current collector, reduces the internal resistance of the battery, and improves the battery's charge and discharge efficiency. The low-impedance electrode structure helps reduce the energy loss of the battery during the charge and discharge process, thereby improving the battery's energy density and overall performance.
[0043] (5) Improving battery cycle stability: Due to the close bonding between the active layer and the current collector, as well as the excellent conductivity and ion transport properties of carbon quantum dots, the battery can maintain stable electrochemical performance during long-term cycle use, reducing capacity attenuation caused by changes in the electrode material structure, thereby improving the battery's cycle stability and service life.
[0044] In summary, the positive electrode provided by the present invention achieves a comprehensive improvement in battery performance, including conductivity, ion transport performance, mechanical stability and cycle stability, by introducing carboxyl-modified carbon quantum dots and optimizing the connection method between the active layer and the current collector, providing an effective technical solution for the development of high-performance lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0046] Figure 1 Schematic diagram of the cross-sectional structure of the positive electrode sheet in the embodiment of the present application;
[0047] Figure 2 Schematic diagram of the connection between the current collector surface and the carbon quantum dots of the positive electrode plate in the embodiment of the present application.
[0048] Reference numerals:
[0049] 100, positive electrode plate; 1, current collector; 2, active layer; 21, carbon quantum dots; 3, functional layer; 31, coating area; 32, non-coating area. DETAILED DESCRIPTION
[0050] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0051] refer to Figure 1 In an embodiment of the present application, a positive electrode sheet is provided, comprising:
[0052] A current collector and an active layer disposed on a surface of the current collector;
[0053] The surface of the current collector contains hydroxyl groups introduced by hydroxyl modification treatment;
[0054] The active layer includes carbon quantum dots and a lithium supplement; the surface of the carbon quantum dots contains carboxyl groups introduced by carboxyl modification treatment;
[0055] The surface of the current collector and the carbon quantum dots in the active layer are connected via ester bonds formed by an esterification reaction between the hydroxyl groups and the carboxyl groups.
[0056] It should be noted that in a battery, a current collector refers to a conductive material used to collect and transmit current, usually made of metal foil (such as aluminum foil, etc.). The current collector plays the role of supporting the electrode material and collecting current in the battery.
[0057] The hydroxyl modification treatment of the above-mentioned current collector can be a surface treatment technology, which introduces hydroxyl (-OH) functional groups on the surface of the current collector by chemical methods. Hydroxyl is a functional group containing oxygen and hydrogen and has strong reactivity.
[0058] Through hydroxyl modification treatment, hydroxyl groups are "introduced" or "added" to the surface of the current collector. These hydroxyl groups can chemically react with other functional groups (such as carboxyl groups) in the electrode material to form stable chemical bonds, thereby enhancing the adhesion between the current collector and the electrode material.
[0059] Specifically, there are different methods for the hydroxyl modification treatment, for example, the steps may include:
[0060] (1) Surface cleaning: First, clean the surface of the current collector to remove impurities and oil stains on the surface.
[0061] (2) Chemical treatment: The current collector is then immersed in a solution containing a hydroxylation agent to introduce hydroxyl groups on the surface of the current collector through a chemical reaction. Commonly used hydroxylation agents include sodium hydroxide, potassium hydroxide, alcohols, etc.
[0062] (3) Cleaning and drying: The treated current collector needs to be cleaned to remove unreacted reagents and by-products, and then dried to obtain a hydroxyl-modified current collector.
[0063] Through hydroxyl modification, the hydroxyl groups introduced on the surface of the current collector can undergo esterification reaction with the carboxyl groups in the electrode material to form a stable ester bond, thereby improving the mechanical stability and electrochemical performance of the electrode. This surface modification technology has important application value in the preparation of battery electrode materials.
[0064] It should be noted that carbon quantum dots (CQDs) are a type of carbon-based zero-dimensional nanomaterials with a size range of 1-10 nanometers. They usually have quasi-spherical or irregular shapes and have unique optoelectronic properties.
[0065] Due to the quantum confinement effect, the electrons and holes of carbon quantum dots are confined to the nanoscale, resulting in different electronic properties from macroscopic materials. Many carbon quantum dots have fluorescent properties and can emit light of different wavelengths. The color of their emission can be adjusted by changing the excitation wavelength or the size of the quantum dots. Carbon quantum dots have good chemical stability and biocompatibility, making them potential for application in biological imaging, sensors and other fields.
[0066] As mentioned above, carboxyl modification treatment is a surface modification technology that introduces carboxyl (-COOH) functional groups on the surface of the material to enhance the surface activity and reactivity of the material.
[0067] As mentioned above, carboxyl is an active functional group that can react with a variety of substances, such as esterification, amidation, etc. Carboxyl modification can increase the surface polarity of the material and improve its dispersibility in polar solvents. Carboxyl modification can enhance the adhesion between the material and other substances (such as polymers, metals, etc.).
[0068] The carbon quantum dots are treated with carboxyl groups to introduce carboxyl groups on the surface. The modified carbon quantum dots can undergo an esterification reaction with the hydroxyl groups on the surface of the current collector to form a stable ester bond, thereby enhancing the adhesion between the active layer and the current collector.
[0069] It should be noted that esterification is an organic chemical reaction in which the hydroxyl group (-OH) of an alcohol (or phenol) reacts with the carboxyl group (-COOH) of a carboxylic acid to produce an ester and water. In the esterification reaction, the oxygen-hydrogen bond and carbon-oxygen double bond between the hydroxyl group and the carboxyl group are broken to form new carbon-oxygen single bonds and oxygen-hydrogen bonds, thereby producing an ester and water.
[0070] refer to Figure 2 The esterification reaction in the embodiments of the present application specifically refers to the reaction between the surface of the current collector (containing hydroxyl groups) after hydroxyl modification and the carboxyl-modified carbon quantum dots (containing carboxyl groups) in the active layer. This reaction can be specifically expressed as:
[0071] R-OH+R'-COOH→RO-CO-R'+H 2 O;
[0072] In the above esterification reaction:
[0073] R-OH represents the current collector surface modified with hydroxyl groups.
[0074] R'-COOH represents the surface of carboxyl-modified carbon quantum dots in the active layer.
[0075] RO-CO-R' represents an ester bond formed by an esterification reaction, which enhances the connection between the current collector and the active layer.
[0076] H 2 O is the water molecule generated by the reaction. It can be removed by drying or other treatments.
[0077] Esterification reactions usually require certain reaction conditions, such as appropriate temperature, catalysts (such as acids or bases), and sometimes the need to remove the generated water to drive the reaction in the direction of ester formation. In the preparation process of battery positive electrode sheets, esterification reactions help form stable chemical bonds, thereby improving the mechanical stability and electrochemical performance of the electrode.
[0078] In summary, the electrode pole piece provided in the embodiment of the present application, the carboxyl-modified carbon quantum dots introduced in the active layer, due to its unique physical and chemical properties, significantly enhance the conductivity of the pole piece, form an efficient electron transmission network, effectively reduce the internal resistance of the battery, and improve the charge and discharge efficiency. At the same time, the high specific surface area and porous structure of these carbon quantum dots provide abundant transmission channels for lithium ions, reduce diffusion resistance, and enhance the rate performance and cycle stability of the battery. Through the esterification reaction between the hydroxyl-modified current collector surface and the carboxyl-modified carbon quantum dots, the ester bond formed further tightly connects the active layer and the current collector, enhances the mechanical stability of the electrode structure, reduces the shedding and peeling of the active material during the charge and discharge process, and prolongs the cycle life of the battery. In addition, the tight ester bond connection also reduces the interface impedance, reduces the internal resistance of the battery, improves the charge and discharge efficiency, reduces energy loss, and improves the energy density and overall performance of the battery.
[0079] Taking all these factors into consideration, the battery prepared by the above-mentioned electrode plates can exhibit excellent electrochemical stability and reduce capacity attenuation during long-term cycle use, thereby significantly improving the cycle stability and service life of the battery.
[0080] Furthermore, the positive electrode sheet further includes a functional layer disposed between the current collector and the active layer;
[0081] The functional layer includes a coating area and a non-coating area;
[0082] The coating region includes an organic polymer;
[0083] In the non-coating area, the active layer is directly connected to the surface of the current collector.
[0084] As mentioned above, a functional layer is provided between the current collector and the active layer. This functional layer has a specific structure, including a coating area and a non-coating area. The coating area is the area coated with the slurry in the functional layer, in which the active layer, the functional layer (coating area) and the current collector are arranged in sequence.
[0085] The non-coating area is the area where the slurry in the functional layer is not coated. In this area, the active layer and the current collector are in direct contact and adhere to each other, that is, the material in the active layer is filled into the non-coating area, so that the material in the active layer is connected to the current collector.
[0086] The coating area contains organic polymers. On the one hand, the organic polymers can improve the bonding force between the current collector and the active layer, and can serve as a waterproof layer to reduce the water content of the positive electrode sheet, because these organic substances can block the contact between the positive electrode active material layer and the moisture in the surrounding environment. For example, during the preparation of the electrode assembly, the active material layer can be blocked from contacting with moisture in the air.
[0087] Therefore, organic polymers can provide additional mechanical support, enhance chemical stability, and / or provide water-repellent properties, thereby protecting the electrode materials and improving the overall performance of the battery.
[0088] In the non-coated area, which is the area not coated with the functional layer slurry, the active layer in this area is directly connected to the surface of the current collector without the intervention of organic polymer. This design allows the active layer to maintain direct contact with the current collector, which helps to improve the efficiency of electron transfer.
[0089] In addition, the positive electrode plate includes a lithium replenisher in the active layer to replenish the lithium ions consumed by the SEI film formed after the first cycle and improve the initial efficiency.
[0090] It should be noted that the lithium supplement agent will inevitably generate alkaline byproducts during the production process. This characteristic makes the lithium supplement agent very easy to absorb water vapor in the air, which leads to poor air stability and easy inactivation. In the embodiment of the present application, the lithium supplement agent in the active layer is in contact with the organic polymer in the coating area, which will further improve the air stability of the lithium supplement agent, thereby improving the initial efficiency of the battery and ensuring the safety of the battery.
[0091] Furthermore, the organic polymer includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyimide, aramid or polyether.
[0092] Furthermore, the coating area also includes porous inorganic material;
[0093] The organic polymer can be fully or partially disposed in the pores of the porous inorganic material.
[0094] The above-mentioned strategy of introducing porous inorganic materials into the positive electrode is to improve the safety performance of the battery, especially in preventing internal short circuits and controlling the temperature rise of the battery. Its purpose and function are:
[0095] The role of porous inorganic materials: Porous inorganic materials are introduced into the coating area. The pore structure of these materials can provide certain mechanical support and spatial isolation inside the battery, which helps to maintain the integrity of the electrode structure.
[0096] Preventing internal short circuits: When the battery is invaded by conductive foreign matter or subjected to other forms of physical damage, porous inorganic materials can act as a barrier layer between the current collector and the active layer, reducing direct contact and thus reducing the risk of internal short circuits.
[0097] Controlling temperature rise: During the operation of the battery, especially under high current charging and discharging conditions, porous inorganic materials can slow down the rapid change of current and suppress the sharp decrease in resistance, thereby controlling the heating rate of the battery and avoiding thermal runaway caused by excessively rapid temperature rise.
[0098] Further, the porous inorganic material includes at least one of aluminum oxide, titanium oxide, zirconium oxide, silicon oxide, manganese oxide, magnesium oxide, nickel oxide, boron nitride, aluminum nitride, magnesium nitride, silicon nitride, aluminum fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride, barium fluoride, aluminum hydroxide and boehmite.
[0099] The use of these porous inorganic materials in batteries can not only improve the physical strength of the battery, but also provide additional protection when abnormal conditions occur in the battery, such as internal short circuit or overheating. Their high thermal stability helps absorb and disperse heat, reducing the risk of thermal runaway, thereby improving the overall safety of the battery.
[0100] In short, by introducing porous inorganic materials into the functional layer coating area of the positive electrode, not only the structural stability and mechanical strength of the electrode are enhanced, but also the safety performance of the battery is effectively improved by controlling the heat generation and temperature rise of the battery under abnormal working conditions. This design helps the battery maintain a more stable and safe working state when facing physical damage or overheating, prolongs the battery life, and reduces potential safety risks.
[0101] Furthermore, the area of the coating region does not exceed 30% of the total surface area of the current collector.
[0102] The above-mentioned limitation on the area of the coating area, i.e., the area of the coating area does not exceed 30% of the total surface area of the current collector, is based on considerations of battery design and performance optimization.
[0103] Although the organic polymer and porous inorganic material in the coating area can provide additional mechanical support, chemical stability and safety, excessive coating may affect the contact between the active layer and the current collector, thereby affecting the electron transmission efficiency. By limiting the area of the coating area, it is possible to ensure that there is a large enough direct contact area between the active layer and the current collector to maintain good electron conduction.
[0104] The use of organic polymers and porous inorganic materials may increase the production cost of the battery. By limiting the area of the coating area, the cost can be controlled while improving the battery performance, achieving a balance between cost and performance.
[0105] The active layer is the main site of the battery's electrochemical reaction and requires sufficient space and contact area for optimal ion and electron transport. Limiting the area of the coating region ensures that the active layer has sufficient uncoated area to support efficient electrochemical reactions.
[0106] During the battery charging and discharging process, the active layer is the main heat generating area. By limiting the area of the coating area, it can ensure that the heat generated by the battery during operation can be effectively dissipated to avoid local overheating, thereby improving the thermal stability and safety of the battery.
[0107] Too large a coating area may affect the overall mechanical stability of the battery electrode. Limiting the area of the coating area helps maintain the flexibility and structural integrity of the electrode and reduce mechanical stress during battery assembly and long-term operation.
[0108] The active layer needs to be in full contact with the electrolyte to achieve good ion transport. Limiting the area of the coating ensures that there is enough space for the electrolyte to penetrate and circulate, thereby improving the battery's charge and discharge performance.
[0109] In summary, limiting the area of the coating zone is intended to optimize the electrochemical performance, thermal management, cost-effectiveness, and mechanical stability of the battery to achieve high-performance, high-safety, and long-life battery design.
[0110] Furthermore, the lithium supplement agent is a nano lithium supplement agent;
[0111] The lithium supplement includes at least one of lithium oxalate, lithium nitride, lithium nickelate, lithium cobaltate and lithium ferrite.
[0112] The cathode plate design with nano lithium supplements aims to comprehensively improve battery performance. Through its high specific surface area and high reactivity, it effectively replenishes the lithium ions consumed when the solid electrolyte interface (SEI) is formed during the first charge of the battery, thereby improving the initial coulombic efficiency. Due to the small size of nano lithium supplements, they can continuously replenish the lithium ions lost by the formation and consumption of the SEI layer during the battery cycle, maintain the battery capacity, and extend the battery life. In addition, the rapid lithium ion release ability of nano lithium supplements helps to improve the rate performance of the battery under high rate charge and discharge conditions. They can also be evenly mixed with electrode materials, optimize the electrode structure, increase the battery charge and discharge rate and reduce polarization, and enhance the electrochemical performance. The use of nano lithium supplements can also reduce the amount of materials required, reduce costs and reduce battery weight. At the same time, the uniform distribution of nano lithium supplements helps to reduce the risk of thermal runaway under overcharge or over-discharge conditions and improve battery safety. This lithium supplement has strong adaptability and can select the most suitable materials according to different battery systems, such as lithium oxalate, lithium nitride, etc., to meet specific electrochemical environments and performance requirements. Overall, the application of nano lithium supplements is to achieve a more efficient, stable and safer battery system, while improving material utilization efficiency and reducing costs.
[0113] In addition, the present application also provides a method for preparing a positive electrode sheet as described in any of the above embodiments, comprising:
[0114] Step S100, coating the surface of the current collector modified with hydroxyl group with active material slurry to obtain a positive electrode plate; wherein the active material slurry includes carbon quantum dots modified with carboxyl group and a lithium supplement agent.
[0115] As mentioned above, the hydroxyl modification treatment is the process of introducing hydroxyl groups into the surface of the current collector, which enhances the chemical bonding force between the current collector and the active layer and helps to improve the structural stability of the electrode.
[0116] Specifically, a chemical treatment method may be used, such as immersing the current collector in a solution containing a hydroxylation agent (eg, a sodium hydroxide solution) to form hydroxyl groups on the surface.
[0117] This treatment enhances the adhesion between the current collector and the active layer, helping to improve the mechanical stability and cycle life of the battery.
[0118] As mentioned above, the active material slurry is a mixture of carboxyl-modified carbon quantum dots and nano lithium supplement agents, which are key components of the active layer of the battery. The carboxyl-modified carbon quantum dots and the nano lithium supplement agent are mixed with a solvent, a binder, etc. to form a uniform slurry. The carboxyl-modified carbon quantum dots improve the conductivity and ion transport performance, and the nano lithium supplement agent helps to improve the initial coulomb efficiency and cycle stability of the battery. Specifically, a ball mill or a high-speed stirrer can be used to mix and disperse the materials to ensure the uniformity of the slurry.
[0119] The active material slurry is evenly coated on the surface of the current collector treated with hydroxyl modification to form an active layer. The slurry can be evenly coated on the current collector using a coating machine, and then the solvent is removed by drying or other methods to solidify into a film, thereby ensuring good contact between the active layer and the current collector and improving the electrochemical performance of the battery. The specific coating can be achieved by methods such as blade coating, roller coating or spraying, and the method to be selected depends on the required coating thickness and uniformity.
[0120] The drying and curing steps are used to remove the solvent in the active material slurry and solidify to form a stable active layer. The current collector coated with the slurry is dried in a controlled environment, such as at a specific temperature and humidity. After the solvent is removed, the contact between the active materials is closer, which helps to improve the conductivity and ion diffusion rate of the battery.
[0121] The drying process can be carried out in an oven, controlling the temperature and time to ensure complete evaporation of the solvent in the slurry while avoiding overheating that may degrade the material's properties.
[0122] Furthermore, the step S100, coating the active material slurry on the surface of the current collector subjected to the hydroxyl modification treatment to obtain the positive electrode sheet, comprises:
[0123] Step S1, immersing the current collector in a solution containing hydroxyl groups, and obtaining the current collector modified with hydroxyl groups after drying;
[0124] The above-mentioned hydroxyl modification treatment of the current collector involves immersing the current collector in a solution containing hydroxyl groups, with the purpose of introducing hydroxyl groups on the surface of the current collector. Usually, a chemical solution such as sodium hydroxide or alcohol is used to form hydroxyl groups on the metal surface through a chemical reaction.
[0125] The resulting current collector surface is rich in hydroxyl groups, which will be used to subsequently form ester bonds with carboxyl groups in the active material.
[0126] The above steps enhance the chemical bonding between the current collector and the active layer, and improve the structural stability and electrochemical performance of the electrode.
[0127] This can be achieved by dipping the current collector into a chemical solution for a certain period of time, then taking it out and drying it.
[0128] Step S2, adding the carboxyl-modified carbon quantum dots and the lithium supplement agent into an organic solvent to dissolve them to obtain the active material slurry; and coating the active material slurry on the surface of the hydroxyl-modified current collector to form an active layer;
[0129] As described above, the carboxyl-modified carbon quantum dots and the lithium supplement agent are added to an organic solvent and dissolved to form a uniform active material slurry.
[0130] The carboxyl-modified carbon quantum dots and the lithium supplement are mixed in a solvent (such as N-methylpyrrolidone or water), and a binder and a conductive agent may also need to be added, so that the resulting slurry is uniform and stable and suitable for coating.
[0131] The above steps ensure the uniform distribution of active materials in the electrode sheet, which helps to improve the charge and discharge performance and cycle stability of the battery.
[0132] Specifically, a stirrer or ultrasonic equipment may be used to mix and disperse the materials to ensure the uniformity of the slurry.
[0133] Step S3, performing drying and rolling processing to obtain the positive electrode sheet.
[0134] As described above, the prepared active material slurry is coated on the surface of the current collector treated with hydroxyl group modification to form an active layer. The slurry can be evenly coated on the current collector using a coating machine to control the thickness and uniformity of the coating, thereby forming a uniform and uniform active layer, which is the key to battery performance.
[0135] The above steps ensure that the battery has highly consistent and repeatable electrochemical performance.
[0136] Specifically, precision coating equipment, such as a knife coater or a roll coater, may be used to achieve precise coating control.
[0137] Furthermore, the active layer also includes positive electrode active material, conductive agent and binder.
[0138] Furthermore, the step S2, before coating the active material slurry, further comprises:
[0139] Step S4, preparing a functional slurry; the functional slurry includes an organic polymer; or the functional slurry includes an organic polymer and a porous inorganic material;
[0140] In the above-mentioned functional slurry, there can be two different slurries:
[0141] (1) Organic polymers;
[0142] (2) Organic polymer and porous inorganic material: wherein the organic polymer can be placed in whole or in part in the pores of the porous inorganic material.
[0143] Step S5, coating the functional slurry on the surface of the current collector treated with hydroxyl group modification, so that a functional layer is formed on the surface of the current collector; the functional layer includes a coating area coated with the functional slurry and a non-coating area not coated with the functional slurry;
[0144] The step S2, coating the active material slurry on the surface of the current collector subjected to the hydroxyl modification treatment to form an active layer, comprises:
[0145] Step S21 , coating the active material slurry on the surface of the coating area and the surface of the non-coating area where the current collector is exposed, to form the active layer.
[0146] In addition, a battery is provided in an embodiment of the present application, comprising a positive electrode sheet as described in any one of the aforementioned embodiments, or a positive electrode sheet obtained by the preparation method as described in any one of the aforementioned embodiments.
[0147] In addition, an electrical device is also provided in an embodiment of the present application, including a battery as described in the aforementioned embodiment.
[0148] As mentioned above, electrical equipment refers to various types of equipment that require batteries as power sources. The batteries described in the embodiments of this application can be widely used in a variety of electrical equipment due to their improved performance, such as enhanced cycle stability, safety, rate performance, etc. For example, they may include but are not limited to: portable electronic devices, computers, electric vehicles, electric bicycles, smart wearable devices, drones, power tools, medical equipment, aerospace equipment, smart home devices, etc.
[0149] The present invention is further described below by means of specific examples, but it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.
[0150] The hydroxyl-modified aluminum foil and carboxyl-modified carbon quantum dots mentioned in the following examples and comparative examples were synthesized by Jiangsu Carbon General New Materials Technology Co., Ltd.
[0151] Example 1
[0152] In this embodiment, the positive electrode sheet is prepared by the following method.
[0153] Experimental methods:
[0154] Prepare hydroxyl-modified aluminum foil, dissolve 4% carboxyl carbon quantum dots, 4% lithium oxalate, 80% NCM (811), 3% CNT, and 9% PVDF in NMP according to the mass ratio to form a positive electrode slurry, coat it on the surface of the hydroxyl-modified aluminum foil, roll and dry it to form an active layer.
[0155] Example 2
[0156] In this embodiment, the positive electrode sheet is prepared by the following method.
[0157] Experimental method: basically the same as that of Example 1, except that lithium oxalate is replaced by aluminum nitride.
[0158] Example 3
[0159] In this embodiment, the positive electrode sheet is prepared by the following method.
[0160] Experimental methods:
[0161] Prepare hydroxyl-modified aluminum foil, partially coat polyvinylidene fluoride on the surface of the aluminum foil to form a functional layer, and the coated area accounts for 30% of the area of the aluminum foil; dissolve 4% carboxyl carbon quantum dots, 4% lithium oxalate, 80% NCM (811), 3% CNT, and 9% PVDF in NMP according to the mass ratio to form a positive electrode slurry, coat it on the surface of the hydroxyl-modified aluminum foil, roll and dry it to form an active layer.
[0162] Example 4
[0163] In this embodiment, the positive electrode sheet is prepared by the following method.
[0164] Experimental method: basically the same as that of Example 3, except that polyvinylidene fluoride is replaced by polytetrafluoroethylene.
[0165] Example 5
[0166] In this embodiment, the positive electrode sheet is prepared by the following method.
[0167] Experimental method: basically the same as Example 3, except that polyvinylidene fluoride is replaced by polyimide.
[0168] Example 6
[0169] In this embodiment, the positive electrode sheet is prepared by the following method.
[0170] Experimental method: basically the same as that of Example 3, except that the coated area accounts for 20% of the area of the aluminum foil.
[0171] Example 7
[0172] In this embodiment, the positive electrode sheet is prepared by the following method.
[0173] Experimental methods:
[0174] Prepare hydroxyl-modified aluminum foil, partially coat polyvinylidene fluoride and alumina on the surface of the aluminum foil to form a functional layer, and the coated area accounts for 30% of the area of the aluminum foil; dissolve 4% carboxyl carbon quantum dots, 4% lithium oxalate, 80% NCM (811), 3% CNT, and 9% PVDF in NMP according to the mass ratio to form a positive electrode slurry, coat it on the surface of the hydroxyl-modified aluminum foil, roll and dry it to form an active layer.
[0175] Example 8
[0176] In this embodiment, the positive electrode sheet is prepared by the following method.
[0177] Experimental method: basically the same as Example 7, except that aluminum oxide is replaced by titanium oxide.
[0178] Comparative Example 1
[0179] In this comparative example, the positive electrode sheet was prepared using the following method.
[0180] Experimental method: basically the same as that of Example 1, except that pure aluminum foil is used.
[0181] Comparative Example 2
[0182] In this comparative example, the positive electrode sheet was prepared using the following method.
[0183] Experimental method: basically the same as that of Example 1, except that carbon-coated aluminum foil was used.
[0184] Comparative Example 3
[0185] In this comparative example, the positive electrode sheet was prepared using the following method.
[0186] Experimental method: basically the same as Example 1, except that the carboxyl carbon quantum dots are replaced with carbon quantum dots.
[0187] Comparative Example 4
[0188] In this comparative example, the positive electrode sheet was prepared using the following method.
[0189] Experimental method: basically the same as Example 1, except that no carboxyl carbon quantum dots are added.
[0190] Comparative Example 5
[0191] In this comparative example, the positive electrode sheet was prepared using the following method.
[0192] Experimental method: basically the same as that of Example 1, except that lithium oxalate is not added.
[0193] Comparative Example 6
[0194] In this comparative example, the positive electrode sheet was prepared using the following method.
[0195] Experimental method: basically the same as that of Example 3, except that pure aluminum foil is used.
[0196] Comparative Example 7
[0197] In this comparative example, the positive electrode sheet was prepared using the following method.
[0198] Experimental method: basically the same as that of Example 3, except that carbon-coated aluminum foil was used.
[0199] Comparative Example 8
[0200] In this comparative example, the positive electrode sheet was prepared using the following method.
[0201] Experimental method: basically the same as Example 3, except that the carboxyl carbon quantum dots are replaced with carbon quantum dots.
[0202] Comparative Example 9
[0203] In this comparative example, the positive electrode sheet was prepared using the following method.
[0204] Experimental method: basically the same as Example 3, except that no carboxyl carbon quantum dots are added.
[0205] Comparative Example 10
[0206] In this comparative example, the positive electrode sheet was prepared using the following method.
[0207] Experimental method: basically the same as Example 3, except that lithium oxalate is not added.
[0208] Comparative Example 11
[0209] In this comparative example, the positive electrode sheet was prepared using the following method.
[0210] Experimental method: basically the same as Example 7, except that pure aluminum foil was used.
[0211] Comparative Example 12
[0212] In this comparative example, the positive electrode sheet was prepared using the following method.
[0213] Experimental method: basically the same as that of Example 7, except that carbon-coated aluminum foil was used.
[0214] Comparative Example 13
[0215] In this comparative example, the positive electrode sheet was prepared using the following method.
[0216] Experimental method: basically the same as Example 7, except that the carboxyl carbon quantum dots are replaced with carbon quantum dots.
[0217] Comparative Example 14
[0218] In this comparative example, the positive electrode sheet was prepared using the following method.
[0219] Experimental method: basically the same as Example 7, except that no carboxyl carbon quantum dots are added.
[0220] Comparative Example 15
[0221] In this comparative example, the positive electrode sheet was prepared using the following method.
[0222] Experimental method: basically the same as Example 7, except that lithium oxalate is not added.
[0223] Comparative Example 16
[0224] In this comparative example, the positive electrode sheet was prepared using the following method.
[0225] Experimental methods:
[0226] A positive electrode slurry is formed by dissolving 80% NCM (811), 7% CNT, and 13% PVDF in NMP in a mass ratio. The slurry is then coated on the surface of an aluminum foil, rolled, and dried to form a positive electrode sheet.
[0227] Preparation of isolation film: polyacrylate is mixed to form a uniform slurry, the slurry is coated on both sides of the porous substrate (polyethylene), and the isolation film is formed after drying.
[0228] Preparation of lithium-ion battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain the electrode assembly. Place the electrode assembly in the outer packaging aluminum plastic film, remove moisture at 80°C, inject the above electrolyte and package, and obtain the lithium-ion battery through the process of formation, degassing, shaping, etc.
[0229] It should be noted that in Examples 1 to 8 and Comparative Examples 1 to 16, the preparation of the negative electrode sheet, the separator, the electrolyte and the lithium-ion battery are the same as in Example 1, and only the preparation of the positive electrode sheet is slightly different. The differences in parameters are shown in the corresponding tables.
[0230] Comparative test experiment:
[0231] 1. Experimental methods:
[0232] (1) Experiment 1-Adhesion test:
[0233] Adhesion test is performed using a universal testing machine, which generally requires at least three parallel samples. Disassemble the electrode assembly, take the fixed position of the electrode assembly (to ensure consistency), cut the isolation membrane and the pole piece (2 layers of isolation membrane and 1 layer of pole piece) at the same time, with a width of 2cm, peel off a layer of isolation membrane, stick double-sided tape (2cm wide) on a steel plate, stick the pole piece surface to the double-sided tape, and first use a 2kg gravity roller to press 3 times. Tear off another layer of isolation membrane by 5mm, stick double-sided tape on the torn isolation membrane, and then stick white paper on the double-sided tape. Install the steel plate to the lower fixture, connect the end of the white paper to the upper fixture, and use the equipment software to operate and read the adhesion value.
[0234] (2) Experiment 2-Electrode conductivity test:
[0235] The positive electrode conductivity of the positive electrode sheet is tested, and the test conditions are: using the Huace high temperature four-probe tester HEST800 instrument to test the conductivity of the positive electrode material surface of the positive electrode sheet.
[0236] Constant current and constant voltage charging, the first cycle charge and discharge voltage is 2.5~4.3V, the current is 0.1C, and the cut-off current is 0.01C. Then, at a rate of 1C, cycle 800 cycles, calculate the cycle capacity retention rate and cycle expansion rate (%), the standard for the qualified cycle performance test is: 800 times capacity retention rate ≥ 80%, cycle expansion thickness ≤ 10%, and calculate the first effect.
[0237] (3) Experiment 3-Electrode moisture test:
[0238] Experimental method: Take about 1g of the electrode and put it into a vial, and use a moisture tester to test the moisture using the Karl Fischer volumetric method. The test temperature is 170°C. (4) Experiment 4-Needle Puncture Test:
[0239] Experimental method: After the single cells are prepared as specified, use a high-temperature resistant steel needle with a diameter of Ф5mm to Ф8mm (the conical angle of the needle tip is 45° to 60°, and the surface of the needle is smooth, free of rust, oxide layer and oil stain) to penetrate from a direction perpendicular to the battery plate at a speed of (25±5)mm / s. The penetration position should be close to the geometric center of the acupuncture surface, and the steel needle stays in the battery; observe for 1h.
[0240] 2. Test results and analysis:
[0241] Table 1. Test results of battery performance prepared in the examples and comparative examples (1)
[0242]
[0243] In Table 1, "Ex." represents examples, and "Comp." represents comparative examples, the same below.
[0244] Referring to the data in Table 1, in Examples 1-2, the hydroxyl-modified aluminum foil and the carboxyl carbon quantum dots in the active layer form ester bonds, which improves the connection force between the active layer and the current collector, thereby reducing the internal resistance of the battery and improving the battery cycle. The presence of lithium oxalate also further improves the initial efficiency of the battery.
[0245] In Comparative Examples 1-4, no ester bonds are formed, and the connection force between the active material and the substrate is weak, so the resistance during the battery cycle is large, affecting the battery cycle and adhesion. Among them, in Comparative Example 4, no carboxyl carbon quantum dots are added, and the lack of them will also affect the conductivity of the positive electrode plate, thereby affecting the battery cycle. In Comparative Example 5, no lithium oxalate is added, and no additional capacity is provided for the battery, which affects the initial efficiency of the battery.
[0246] Table 2. Test results of battery performance prepared in the examples and comparative examples (2)
[0247]
[0248] Referring to the data in Table 2, in Examples 3-6, the hydroxyl-modified aluminum foil and the carboxyl carbon quantum dots in the active layer form ester bonds, which improves the connection force between the active layer and the current collector, thereby reducing the internal resistance of the battery and improving the battery cycle. In addition, a functional layer is added, and the organic polymer in the functional layer will densely cover the surface of the positive electrode, which can block the contact between the active material layer of the positive electrode plate and the moisture in the air, and finally play a role in reducing the water content of the positive electrode plate. The presence of lithium oxalate also further improves the initial efficiency of the battery.
[0249] In Comparative Example 6, pure aluminum foil is used, no ester bonds are formed, and the connection force between the active material and the substrate is weak, so the resistance during the battery cycle is large, affecting the battery cycle and adhesion.
[0250] Comparative Example 7 uses carbon-coated aluminum foil, and no ester bond is generated. The connection between the active material and the substrate is weak, so the resistance during the battery cycle is large, affecting the battery cycle and adhesion, but the carbon-coated aluminum foil will increase the conductivity of the electrode.
[0251] Comparative Example 8 uses carbon quantum dots, which can effectively improve the conductivity of the electrode, thereby affecting the battery cycle effect to a certain extent. However, the carbon quantum dots cannot generate ester bonds, and the connection between the active material and the substrate is weak, which affects the battery cycle and adhesion to a certain extent.
[0252] In Comparative Example 9, no carboxyl carbon quantum dots were added, and ester bonds could not be generated. The connection between the active material and the substrate was weak, resulting in a large resistance during the battery cycle, which affected the battery cycle and adhesion. In addition, carboxyl carbon quantum dots have excellent conductivity, and their absence would also affect the conductivity of the positive electrode.
[0253] In Comparative Example 10, lithium oxalate is not added, and no additional capacity is provided for the battery, which affects the initial efficiency of the battery.
[0254] In Example 1, no active layer is added, which cannot reduce the water content of the positive electrode plate.
[0255] Table 3. Test results of battery performance obtained in Examples and Comparative Examples (3)
[0256]
[0257] In Examples 7-8, the hydroxyl-modified aluminum foil and the carboxyl carbon quantum dots in the active layer form an ester bond, which increases the connection between the active layer and the current collector, thereby reducing the internal resistance of the battery and improving the battery cycle. In addition, a functional layer is added, and the organic polymer and porous inorganic material in the functional layer will cover the positive electrode surface more densely, which can block the contact between the active material layer of the positive electrode and the moisture in the air, and finally play a role in reducing the water content of the positive electrode. The pore structure of these porous inorganic materials can provide certain mechanical support and spatial isolation inside the battery, which helps to maintain the integrity of the electrode structure and improve the safety of the battery. The presence of lithium oxalate also further improves the first effect of the battery.
[0258] Comparative Example 11 uses pure aluminum foil, and no ester bond is generated. The connection between the active material and the substrate is weak, and the resistance during the battery cycle is large, which affects the battery cycle and adhesion.
[0259] Comparative Example 12 uses carbon-coated aluminum foil, and no ester bond is generated. The connection between the active material and the substrate is weak, so the resistance during the battery cycle is large, affecting the battery cycle and adhesion, but the carbon-coated aluminum foil will increase the conductivity of the electrode.
[0260] Comparative Example 13 uses carbon quantum dots, which can effectively improve the conductivity of the electrode, thereby affecting the cycle effect of the battery to a certain extent. However, the carbon quantum dots cannot generate ester bonds, and the connection between the active material and the substrate is weak, which affects the cycle and adhesion of the battery to a certain extent.
[0261] In Comparative Example 14, no carboxyl carbon quantum dots were added, and ester bonds could not be generated. The connection between the active material and the substrate was weak, and the resistance during the battery cycle was large, affecting the battery cycle and adhesion. In addition, carboxyl carbon quantum dots have excellent conductivity, and their absence will also affect the conductivity of the positive electrode.
[0262] In Comparative Example 15, lithium oxalate is not added, and no additional capacity is provided for the battery, which affects the initial efficiency of the battery.
[0263] Table 4. Test results of battery performance obtained in Examples and Comparative Examples (4)
[0264]
[0265] In Comparative Example 16, no ester bond was generated and a lithium supplement was added, so the comprehensive conductivity and cycle performance were average.
[0266] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode sheet, characterized in that: include: A current collector and an active layer disposed on a surface of the current collector; The surface of the current collector contains hydroxyl groups introduced by hydroxyl modification treatment; The active layer includes carbon quantum dots and a lithium supplement; the surface of the carbon quantum dots contains carboxyl groups introduced by carboxyl modification treatment; The surface of the current collector and the carbon quantum dots in the active layer are connected via ester bonds formed by an esterification reaction between the hydroxyl groups and the carboxyl groups.
2. The positive electrode sheet according to claim 1, characterized in that: The positive electrode sheet further includes a functional layer disposed between the current collector and the active layer; The functional layer includes a coating area and a non-coating area; The coating region includes an organic polymer; In the non-coating area, the active layer is directly connected to the surface of the current collector.
3. The positive electrode sheet according to claim 2, characterized in that: The organic polymer includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyimide, aramid or polyether.
4. The positive electrode sheet according to claim 2, characterized in that: The coating area also includes a porous inorganic material; The organic polymer can be fully or partially disposed in the pores of the porous inorganic material.
5. The positive electrode sheet according to claim 4, characterized in that: The porous inorganic material includes at least one of aluminum oxide, titanium oxide, zirconium oxide, silicon oxide, manganese oxide, magnesium oxide, nickel oxide, boron nitride, aluminum nitride, magnesium nitride, silicon nitride, aluminum fluoride, lithium fluoride, sodium fluoride, magnesium fluoride, calcium fluoride, barium fluoride, aluminum hydroxide and boehmite.
6. The positive electrode sheet according to claim 2, characterized in that: The area of the coating region does not exceed 30% of the total surface area of the current collector.
7. The positive electrode sheet according to claim 1, characterized in that: The lithium supplement agent is a nano lithium supplement agent; The lithium supplement includes at least one of lithium oxalate, lithium nitride, lithium nickelate, lithium cobaltate and lithium ferrite.
8. A method for preparing a positive electrode sheet according to any one of claims 1 to 7, characterized in that: include: An active material slurry is coated on the surface of the current collector treated with hydroxyl group modification to obtain a positive electrode plate; wherein the active material slurry includes carbon quantum dots treated with carboxyl group modification and a lithium supplement agent.
9. The method for preparing a positive electrode sheet according to claim 8, characterized in that: The method of coating the active material slurry on the surface of the current collector treated with hydroxyl group modification to obtain a positive electrode sheet comprises: The current collector is immersed in a solution containing hydroxyl groups, and after drying, the current collector modified with hydroxyl groups is obtained; The carbon quantum dots and the lithium supplement agent are added into an organic solvent and dissolved to obtain the active material slurry; and the active material slurry is coated on the surface of the current collector treated with hydroxyl group modification to form an active layer; The positive electrode sheet is obtained by drying and rolling.
10. The method for preparing a positive electrode sheet according to claim 9, characterized in that: The active layer also includes positive electrode active material, conductive agent and binder.
11. The method for preparing a positive electrode sheet according to claim 10, characterized in that: Before coating the active material slurry, the method further comprises: Prepare a functional slurry; the functional slurry includes an organic polymer; or the functional slurry includes an organic polymer and a porous inorganic material; The functional slurry is coated on the surface of the current collector treated with hydroxyl group modification, so that a functional layer is formed on the surface of the current collector; the functional layer includes a coating area coated with the functional slurry and a non-coating area not coated with the functional slurry; The active material slurry is coated on the surface of the current collector treated with hydroxyl group modification to form an active layer, comprising: The active material slurry is coated on the surface of the coating area and the surface of the non-coating area where the current collector is exposed to form the active layer.
12. A battery, characterized in that: It comprises the positive electrode sheet as described in any one of claims 1 to 7, or the positive electrode sheet obtained by the preparation method as described in any one of claims 8 to 11.
13. An electrical equipment, characterized in that: Comprising the battery of claim 12.
Citation Information
Patent Citations
Preparation method for lithium ion battery pole piece and lithium ion battery pole piece
CN110808356A
Lithium supplement agent and preparation method thereof, positive electrode material and lithium ion battery
CN117525635A